The Impact of a One Laptop per Child Program on Learning: Evidence from Uruguay - Gioia De Melo; Alina Machado; Alfonso Miranda (Institute for the Study of Labor (IZA), 2014)
We present evidence on the impact on students' math and reading scores of one of the largest deployments of an OLPC program and the only one implemented at a national scale: Plan Ceibal in Uruguay. Unlike previous work in the field, we have unique data that allow us to know the exact date of laptop delivery for every student in the sample. This gives us the ability to use a continuous treatment, where days of exposure are used as a treatment intensity measure. We use a panel data framework including fixed effects at the individual level. Given that there is some variation in the date of laptop delivery across individuals within the same school, we can identify the effect of the program net of potential heterogeneity in the rate schools gain improvements on student's achievement over time in the absence of the OLPC program across the country (i.e. we allow each school to follow a different learning growth curve over time due to unobservable time-varying heterogeneity). We also run an alternative specification where we allow for different learning growth curves over time between schools located in Montevideo and the rest of Uruguay. Our results suggest that in the first two years of its implementation the program had no effects on math and reading scores. The zero effect could be explained by the fact that laptops in class are mainly used to search for information on the internet.
Keywords: I21; I28; 330; impact evaluation; education; technology